Analisa Kepuasan Pelanggan Terhadap Pelayanan Jasa Mutiara Laundry Dengan Metode Customer Satisfaction Index - Rizky Rinaldi (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2024)
One that affects the increase and decrease in customers is the level of customer satisfaction in service, there are often complaints that occur from customers who use laundry services who are harmed by the negligence of laundry service providers. Therefore it is necessary to have a system that is able to analyze the level of customer satisfaction and service indicators to customers so that the laundry services can evaluate each month the services that have been provided by the laundry services. Decision support systems are the intellectual counterpart of human resources that run on computer capabilities in making a decision. There are many methods that can be used in decision support systems, one of which is the Customer Satisfaction Index (CSI) method. The Customer Satisfaction Index (CSI) method is an index to determine the overall level of customer satisfaction with an approach that takes into account the level of importance of the measured product or service attributes. Based on the results of this study it is known that the Customer Satisfaction Index (CSI) method can assist in the process of analyzing the level of customer satisfaction with Mutiara Laundry services. The application of the Customer Satisfaction Index (CSI) method in this decision support system is able to provide good results so that it can make it easier for Mutiara Laundry Batang Kuis to analyze the level of customer satisfaction.